EXPLORING THE IMPACT OF TEACHER PROFESSIONAL DEVELOPMENT ON TEACHERS` PERFORMANCE: A LITERATURE REVIEW STUDY - Chen Yueqin, Lubna Ali Mohammed (Chelonian Research Foundation, 2023)
The central purpose that education serves at all levels is to ensure promotion of high quality of teaching as well as the learning process. Teachers themselves are trained with an objective of transferring their skills as well as knowledge to students to cultivate a distinctive character in the students that can be diverse enough to fit in the diverse global society. In this way the performance of teachers has remained a critical aspect in the evaluation of teachers` professional training and the capacity that it has in meeting its core objectives. It is in this respect that a literature review of the various research analysis that have been conducted on this subject and the findings which have been made in the process remains to be the central aim of this analytical work. The finding made by this analysis will also help in informing future evaluations on the subject hence giving the right trajectory of the analysis. In this respect, this analysis has been able to establish that, professional development for teachers is considered to be indispensable aspect of teachers` ability to deliver quality in their services as well as in their engagement. Professional development does encompass a wide array of things which can include but are not limited to taking part in different courses, conducting reflections in the teaching approaches that teachers themselves undertakes, making observations of the approaches that other teachers are utilizing as part of their teaching initiatives as well as engaging in conversation with fellow teachers both after and before teaching.